An Innovative Approach to Implementing a Green Economy Through Javanese Local Wisdom in Elementary School Learning - Setiawan, Bramianto; Mukhlis, Septian; Dea Nur Hafifah; Zulela MS; Iasha, Vina (EduBase : Journal of Basic Education, 2025)
Objective: This study examines the implementation of Green Economy concepts through Cultural-Based Learning in Indonesian elementary schools, focusing specifically on Javanese cultural contexts. Novelty: Addressing a critical gap in sustainability education, the study demonstrates how integrating local traditions can effectively contextualize global sustainability goals in the classroom. Methods: The study uses a mixed-methods design, surveying 200 teachers across four provinces in Java and conducting in-depth interviews with 30 participants. Results: Quantitative findings indicate strong teacher understanding of Green Economy principles (M=4.12/5), but relatively lower application levels (M=3.89), with significant regional disparities (F=3.864, p=0.010). Qualitative analysis reveals three main themes: (1) teacher commitment to environmental stewardship, (2) systemic barriers such as curriculum overload and limited facilities, and (3) the role of Javanese cultural practices—such as Sedekah Bumi—in enhancing student engagement. Conclusions: Practical implications include the development of culturally responsive curricula and targeted teacher training programs. The study is limited to the Javanese region, and further research is needed to explore its applicability in other cultural settings.